Agama dan Sinema: Sebuah Dialog Interkultural - Bawono, Haryo Tejo (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2010)
A relation can be mapped between religion and cinema. More than a superficial discourse, this relation appears as an intercultural dialogue, a kind of reflective and critical dialogue. At the end of the ongoing conversation we eventually can hope that religion, as well as cinema, may remain as a quest and construction of meanings rooted in the day-to-day life, which is supposed to be very normal without being banal, vulgar without being filthy.